Biomarkers of neonatal stress assessment: A prospective study. (October 2019) - Rouatbi, H.; Zigabe, S.; Gkiougki, E.; Vranken, L.; Van Linthout, C.; Seghaye, M.-C.
Abstract: Introduction: Early diagnosis of perinatal asphyxia, the major cause of neonatal mortality and morbidity, might be improved by the detection of neonatal stress biomarkers such as cardiac troponin (CTn)T, CTnI, NT-Terminal-pro-Brain Natriuretic Peptide (NT-pro-BNP), copeptin, and high sensitivity C-reactive protein (hs-CRP). However, reference values in neonates are lacking. The objective of our study was therefore to establish a reference range of these biomarkers in healthy full term newborns and to analyze the influence of delivery mode on their cord blood concentrations. Patients and methods: CTnT, CTnI, NT-pro-BNP, Copeptin and hs-CRP levels were determined in 201 neonates enrolled in this prospective study and correlated to the delivery mode and post-natal outcome. Results: Using the 99th percentile, the upper reference limit in healthy newborns was established for all biomarkers. Neonates born after complicated delivery had significantly higher values of CTnT, CTnI and Copeptin than those born after uncomplicated delivery. In the multiple regression models with CTnT as dependent variable, the delivery mode was the statistically significant independent variable. Conclusion: In this study, we established reference values of cord blood concentrations of cardiac stress biomarkers in healthy newborns. We showed that cardiac-related birth stress is dependent on delivery mode. Highlights: Early diagnosis of birth stress may be improved by cord blood concentrations of biomarkers of organ damage in neonates We provide reference values of cord blood concentrations of cardiac stress biomarkers in healthy newborns Our results indicate that cardiac-related birth stress is clearly dependent on delivery mode